Penerapan Metode Jarimatika di TK Asoka Makassar - Mersilina Luther Patintingan (LPPM UKI Toraja, 2017)
This study aimed to determine (1) description of the application of the method Jarimatika in early childhood learning in kindergarten Asoka Makassar, (2) difficulty and ease gained in applying the method in kindergarten Asoka Jarimatika Makassar. Type of research is action research is descriptive qualitative. In this case the researcher wants to describe things related to the application of methods in kindergarten Asoka Jarimatika Makassar. Data collection method is a method of observation, interviews, and documentation. Step-by-step analysis of the data, namely data collection, data reduction, data presentation, and conclusion. The results showed that (1) the application Jarimatika (Mathfingers) method in kindergarten Asoka Makassar through three stages Enaktif stage, stage Iconic and Symbolic Stage. For stage Enaktif some things that teachers do to introduce numbers and counting as starters by using concrete objects and events or real events that were around the child. The usual methods of learning are combined storytelling, demonstration (performance) and experiment. For Iconic Stage teacher displays knowledge learned through the images and symbolic stage where teachers began incorporating the image is meant by the symbol. (2) Constraints faced by teachers in implementing this method is twofold Jarimatika a) sourced from teachers include: Limitations of teachers in relation to media images presented symbol jarimatika b) the use of plain language for students c) limited insight in answering each question and the needs of learners, and students who come from: a) inferior and do not have the confidence b) the nature of egocentric children so often scrambling to his attention and objects c) children akt and difficult to focus for a long time. Ease obtained teacher also includes 2 (two) things: a) that comes from the teacher that the teacher is no longer overwhelmed in providing instructional media b) this method gives pleasure and enthusiasm in children the teacher is no longer difficult to condition children to be ready to learn.